2017
DOI: 10.1177/0892705717738287
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic flame retardant effect between nano-silicon dioxide and layered double hydroxides in ethylene vinyl acetate composites

Abstract: Layered double hydroxides (LDHs) were synthesized by a coprecipitation method. The synergistic flame retardant effect of nano-silicon dioxide (nano-SiO2) on ethylene vinyl acetate (EVA)/LDHs composites was studied using limiting oxygen index (LOI), cone calorimeter test (CCT), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). Results showed that the LOI values of the EVA/LDHs/nano-SiO2 composites were basically higher than that of the EVA/LDHs composite, and the EVA composite with 48% L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…In this study, the untreated CF and CF treated with EVA (CF/EVA) showed similar LOI values of 18.8% and 19% respectively indicating that the CF and CF/EVA ignited easily in air. It was reported that the LOI value of EVA was 19.2% [17]. It can be seen that the LOI values of treated CF/EVA increased rapidly by the addition of SiO 2 and/or Al 2 O 3 from 19 to 29.3% and suggesting a synergistic effect and developing the flame resistance properties which is helpful to the LOI test.…”
Section: Flame Retardant Application Of Treated Cfmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, the untreated CF and CF treated with EVA (CF/EVA) showed similar LOI values of 18.8% and 19% respectively indicating that the CF and CF/EVA ignited easily in air. It was reported that the LOI value of EVA was 19.2% [17]. It can be seen that the LOI values of treated CF/EVA increased rapidly by the addition of SiO 2 and/or Al 2 O 3 from 19 to 29.3% and suggesting a synergistic effect and developing the flame resistance properties which is helpful to the LOI test.…”
Section: Flame Retardant Application Of Treated Cfmentioning
confidence: 83%
“…Silicon dioxide is one of the reinforced filling materials that are widely utilized as an improving agent in thermoplastic polymers that improves the mechanical properties [16] and has synergistic flame retardant property [17,18]. SiO 2 is known as a potential and safe flame retardant additive for polymer systems due to its high heat resistance, inert and non-toxic features [19].…”
Section: Introductionmentioning
confidence: 99%
“…Flame retardants of inorganic nature such as nanosilica, nano alumino-silica, nano clay are often used to cover the fabric surface to create an insulating and fireproof protective layer and simultaneously, the physico-mechanical properties can be improved. Among inorganic flame retardants, nano silica and nano titanium dioxide have received a great interest because these materials are environmentally friendly, non-toxic and highly effective in slowing or resisting fire [9][10][11][12]. El-Shafei et al [13] modified the fabric with nano TiO 2 sol gel from titanium isopropoxide and the fire resistance of the TiO 2 modified fabric is significantly improved (LOI increased from 17.4% to 23%).…”
Section: Introduction *mentioning
confidence: 99%
“…20,21 Ethylene vinyl acetate (EVA) copolymer, as elastomer material, has many advantages in high impact resistance, water resistance, and processability. 9,22 EVA can be used as the compatibilizer, which can enhance the interface adhesion between inorganic particles and polymer matrix. In this work, a novel method of organic modification of EG is proposed by using grafting process containing phosphorous and synergistic effect with ZB applying to the HDPE/EVA composites filled with MH/ATH.…”
Section: Introductionmentioning
confidence: 99%